Parenting while working from home : a monthly guide to help parents balance their careers, connect with their kids, establish their inner strength - Medini, Shari; Tunis, Karissa (Skyhorse Publishing, 2021)
As more parents work from home than ever before, there are unique challenges when it comes to meeting the demands of their job, helping their kids thrive, and finding even five minutes to take care of themselves. Parenting While Working from Home offers tips, strategies, and reflections to help parents balance their careers, connect with their kids, and establish their inner strength over the course of a year.